ECCD-F1KD situation analysis in selected KOICA-UNICEF municipalities in Northern Samar - Connie Bayudan-Dacuycuy; Lora Kryz Baje; Maria Alma Mariano (Philippine Institute for Development Studies (PIDS), 2019)
This report examines the context, practices, and strategies in selected KOICA municipalities in Northern Samar. Using the Nurturing Care Framework, it analyzes how these LGUs implement and govern ECCD-F1KD initiatives. It also analyzes the factors and processes that influence the implementation and delivery of, and access to ECCD-F1KD services, and provides recommendations on strategies and related interventions for the ECCD-F1KD Program. To do these, this report conducts a situation analysis of nutrition and health outcomes and provides recommendations on three elements, namely, enabling environment, supply, and demand.
Keywords: 330; Kinder; Kinderarmut; Gesundheitsversorgung; Ernährungssicherung; Armutsbekämpfung; Philippinen